2017
DOI: 10.1126/science.aaf4918
|View full text |Cite
|
Sign up to set email alerts
|

A central neural circuit for itch sensation

Abstract: Although itch sensation is an important protective mechanism for animals, chronic itch remains a challenging clinical problem. Itch processing has been studied extensively at the spinal level. However, how itch information is transmitted to the brain and what central circuits underlie the itch-induced scratching behavior remain largely unknown. We found that the spinoparabrachial pathway was activated during itch processing and that optogenetic suppression of this pathway impaired itch-induced scratching behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
183
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(198 citation statements)
references
References 41 publications
13
183
1
1
Order By: Relevance
“…Therefore, CGRP PBN neurons can be activated by non-painful noxious stimuli and their activation is required to elicit appropriate behavioral responses. These findings identify a specific population of PBN neurons that contribute to itch-related behavior 20 .…”
Section: Resultsmentioning
confidence: 72%
“…Therefore, CGRP PBN neurons can be activated by non-painful noxious stimuli and their activation is required to elicit appropriate behavioral responses. These findings identify a specific population of PBN neurons that contribute to itch-related behavior 20 .…”
Section: Resultsmentioning
confidence: 72%
“…In recent years, great progress has been made toward understanding itch‐related neuronal circuitry. A growing body of literature has demonstrated that the peripheral nervous system, including TRPV1‐positive (Imamachi et al, ) and TRPA1‐positive (Wilson et al, ) primary afferent neurons, central neural circuits, including GRPR (Sun & Chen, ) positive neurons and the spinothalamic tract (Andrew & Craig, ), as well as the spinoparabrachial pathway (Mu et al, ), all contribute to itch. In addition to the neuronal basis of the itch sensation, astrocytes are considered new players in chronic itch.…”
Section: Discussionmentioning
confidence: 99%
“…3 GRPR neurons may form contacts with NK1R neurons which project to the parabrachial nucleus (PBN) and the spinothalamic track (STT) neurons to relay itch information in mice (Akiyama et al, 2015;Cameron et al, 2015;Mu et al, 2017). Although some information about GRPR neurons have been obtained using indirect approaches or transgenic mice which may not fully recapitulate Grpr expression in the spinal cord (Aresh et al, 2017;Wang et al, 2013), direct characterization of molecular, anatomical and electrophysiological properties of GRPR neurons are yet to be achieved.…”
Section: Introductionmentioning
confidence: 99%